Complete transthoracic resection of giant posterior mediastinal goiter: case report and review of surgical strategies - Zhao, Honglin (Onco Targets Ther, 2016)
Intrathoracic goiters generally occupy anterior mediastinum, rarely involving the posterior mediastinal space. Reported herein is a 54-year-old female with a giant posterior mediastinal mass that was successfully resected via right posterolateral thoracotomy. The final pathologic diagnosis was giant posterior mediastinal goiter. This patient has done well postoperatively, with no evidence of local recurrence at 12-month follow-up. Related surgical strategies in past publications are summarized.